Microbiome Profiling Reveals a Microbial Dysbiosis During a Natural Outbreak of Tenacibaculosis (Yellow Mouth) in Atlantic Salmon - Wynne, James W.; Thakur, Krishna K.; Slinger, Joel; Samsing, Francisca; Milligan, Barry; Powell, James F. F.; McKinnon, Allison; Nekouei, Omid; New, Danielle; Richmond, Zina; Gardner, Ian; Siah, Ahmed (Frontiers in Microbiology, 2020)
Tenacibaculosis remains a major health issue for a number of important aquaculture species globally. On the west coast of Canada, Yellow mouth (YM) disease is responsible for significant economic loss to the Atlantic salmon industry. While Tenacibaculum maritimum is considered to be the primary agent of clinical YM, the impact of YM on the resident microbial community and their influence on the oral cavity is poorly understood. Using a 16s rRNA amplicon sequencing analysis the present study demonstrates a significant dysbiosis and a reduction in diversity of the microbial community in the YM affected Atlantic salmon. The microbial community of YM affected fish was dominated by two amplicon sequence variants (ASVs) of T. maritimum, although other less abundant ASVs were also found. Interestingly clinically unaffected (healthy) and YM surviving fish also had a high relative abundance of T. maritimum, suggesting that the presence of T. maritimum is not solely responsible for YM. A statistically significant association was observed between the abundance of T. maritimum and increased abundance of Vibrio spp within fish displaying clinical signs of YM. Findings from our study provides further evidence that YM is a complex multifactorial disease, characterised by a profound dysbiosis of the microbial community which is dominated by distinct ASVs of T. maritimum. Opportunistic taxa, including Vibrio spp., may also play a role in clinical disease progression.